Renewable energy investment risk assessment for nations along China's Belt & Road Initiative: An ANP-cloud model method. (1st January 2020) - Wu, Yunna; Wang, Jing; Ji, Shaoyu; Song, Zixin
Abstract: With the active promotion of the "Belt & Road initiative", renewable energy investment shows the market prospect of explosive growth in various countries. However, the overseas renewable energy investment risks faced by Chinese companies are synthesized, variegated and long-term, requiring comprehensive assessments and joint responses. To evaluate the risks in renewable energy investment for nations along "Belt & Road initiative", this paper establishes an ANP-cloud framework in consideration of the randomness of information. Firstly, 32 risk factors covering technical, political, economic, resource, social/environmental risks and Chinese factors are identified and 54 nations are studied and classified into six groups. Then, the analytic network process (ANP) method is employed to determine four sets of weights based on grouping, so that mutual influence among factors can be taken into account. Furthermore, the overall risks are calculated through the cloud model according to their membership degree. The results indicate that political risks, economic risks and resource risks occupy the main determinant position during the overseas renewable energy investment while Chinese factors have certain effects on investment behaviors. Finally, recommendations are given for investors and decision-makers to help choose a more appropriate nation to invest in, strengthen risk prevention and control as well. Highlights: Renewable energy investment risk assessment for nations along Belt & Road Initiative is studied. Four sets of weights are determined for different national conditions. Evaluation index system including Chinese factors is built. Investment recommendations are provided according to the risk level of countries.